PENINGKATAN HASIL BELAJAR SISWA KELAS X SMAN 7 BONE MELALUI MODEL PEMBELAJARAN STUDENT CENTERED LEARNING (SCL) PADA MATERI TEKS NEGOSIASI - Syahrani, Audya; Sua, Andi Tenri; Suhardiman, Suhardiman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the low learning outcomes of tenth-grade students at SMAN 7 Bone on negotiation texts. Pre-cycle data showed an average score of only 58.96 (poor) and 42% of students failed to meet the Minimum Competency (KKM) due to passive teacher-centered learning. The focus of this research is to improve learning outcomes and student engagement through the implementation of the Student-Centered Learning (SCL) model. This study used the Classroom Action Research (CAR) method, conducted in two cycles with 27 students. The research stages included planning, SCL implementation with group discussions and negotiation practice, observation of engagement, and a learning outcome test at the end of each cycle, with a success indicator of 85% completion. The results showed progressive and significant improvement. In Cycle I, the average score increased to 70.92 (sufficient), but reflections showed that students remained passive during presentations. After strategy improvements and more intensive teacher guidance in Cycle II, the average score jumped to 91.33 (very good), with classical completion reaching 100%. The main finding is that actively facilitated SCL successfully increased students' enthusiasm and courage in arguing. It was concluded that the SCL model was highly effective in improving student learning outcomes in negotiation texts. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya hasil belajar siswa kelas X SMAN 7 Bone pada materi teks negosiasi, di mana data pra-siklus menunjukkan nilai rata-rata hanya 58,96 (kategori kurang) dan 42% siswa tidak tuntas KKM akibat pembelajaran teacher-centered yang pasif. Fokus penelitian ini adalah untuk meningkatkan hasil belajar dan keaktifan siswa melalui penerapan model Student Centered Learning (SCL). Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus terhadap 27 siswa. Tahapan penelitian meliputi perencanaan, pelaksanaan SCL dengan diskusi kelompok dan praktik negosiasi, observasi keaktifan, serta tes hasil belajar di akhir setiap siklus dengan indikator keberhasilan 85% tuntas. Hasil penelitian menunjukkan peningkatan yang progresif dan signifikan. Pada Siklus I, nilai rata-rata meningkat menjadi 70,92 (cukup), namun refleksi menunjukkan siswa masih pasif saat presentasi. Setelah perbaikan strategi dan bimbingan guru yang lebih intensif pada Siklus II, terjadi lonjakan nilai rata-rata menjadi 91,33 (sangat baik), dengan ketuntasan klasikal mencapai 100%. Temuan utama adalah SCL yang terfasilitasi aktif berhasil meningkatkan antusiasme dan keberanian siswa berargumentasi. Disimpulkan bahwa model SCL sangat efektif dalam meningkatkan hasil belajar siswa pada materi teks negosiasi.